Is Eco-Anxiety Racial Anxiety?: Harnessing Eco-Anxiety for Practicing Racial and Climate Justice - Cho, Eunil David (Practical wisdom in the living web of the anthropocene, 2025)
This essay aims to invite practical theologians to consider racial injustice seriously as they continue deepening practical theological scholarship on climate change and environmental crises. By looking at the specific issue of eco-anxiety, I examine how scholars and practitioners must consider how climate change and eco-anxiety are not uniformly experienced in the United States. While communities of color suffer eco-anxiety disproportionately more, their voices and experiences have been largely absent in the larger conversation. Subsequently, I look at Fannie Lou Hamer’s practical theological work of ecological justice in order to suggest how practical theologians need to empower individuals and communities to harness their experience of eco-anxiety for practicing climate and racial justice.